Desensitization of the Neurokinin-1 Receptor (NK1-R) in Neurons: Effects of Substance P on the Distribution of NK1-R, G(αq/11), G-Protein Receptor Kinase-2/3, and β-Arrestin-1/2 - McConalogue, Karen (The American Society for Cell Biology, 1998)
Observations in reconstituted systems and transfected cells indicate that G-protein receptor kinases (GRKs) and β-arrestins mediate desensitization and endocytosis of G-protein–coupled receptors. Little is known about receptor regulation in neurons. Therefore, we examined the effects of the neurotransmitter substance P (SP) on desensitization of the neurokinin-1 receptor (NK1-R) and on the subcellular distribution of NK1-R, G(αq/11), GRK-2 and -3, and β-arrestin-1 and -2 in cultured myenteric neurons. NK1-R was coexpressed with immunoreactive G(αq/11), GRK-2 and -3, and β-arrestin-1 and -2 in a subpopulation of neurons. SP caused 1) rapid NK1-R–mediated increase in [Ca(2+)](i), which was transient and desensitized to repeated stimulation; 2) internalization of the NK1-R into early endosomes containing SP; and 3) rapid and transient redistribution of β-arrestin-1 and -2 from the cytosol to the plasma membrane, followed by a striking redistribution of β-arrestin-1 and -2 to endosomes containing the NK1-R and SP. In SP-treated neurons G(αq/11) remained at the plasma membrane, and GRK-2 and -3 remained in centrally located and superficial vesicles. Thus, SP induces desensitization and endocytosis of the NK1-R in neurons that may be mediated by GRK-2 and -3 and β-arrestin-1 and -2. This regulation will determine whether NK1-R–expressing neurons participate in functionally important reflexes.